2021
DOI: 10.1038/s41423-021-00735-3
|View full text |Cite
|
Sign up to set email alerts
|

IFNγ signaling integrity in colorectal cancer immunity and immunotherapy

Abstract: The majority of colorectal cancer patients are not responsive to immune checkpoint blockade (ICB). The interferon gamma (IFNγ) signaling pathway drives spontaneous and ICB-induced antitumor immunity. In this review, we summarize recent advances in the epigenetic, genetic, and functional integrity of the IFNγ signaling pathway in the colorectal cancer microenvironment and its immunological relevance in the therapeutic efficacy of and resistance to ICB. Moreover, we discuss how to target IFNγ signaling to inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 123 publications
(134 reference statements)
2
48
0
3
Order By: Relevance
“…On the other hand, analysis results indicated that the interferon-γ (IFN-γ) response pathway was negatively correlated with glycerolipid metabolism in colon cancer. The IFN-γ signaling pathway plays a critical role in anticancer immunity mainly through anti-proliferation ( 38 ), apoptosis ( 39 ), necrosis ( 40 ), and ferroptosis ( 41 ); however, it is also reported that IFN-γ induces the expression of immune checkpoints which may lead to an immune-suppression microenvironment, and this was consistent with our further analysis about the immune microenvironment ( 42 44 ). Taken together, our results suggested that the IFN-γ response pathway might mainly contribute to the immune-suppression microenvironment in glycerolipid metabolism-activated colon cancer, other than antitumor effect.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, analysis results indicated that the interferon-γ (IFN-γ) response pathway was negatively correlated with glycerolipid metabolism in colon cancer. The IFN-γ signaling pathway plays a critical role in anticancer immunity mainly through anti-proliferation ( 38 ), apoptosis ( 39 ), necrosis ( 40 ), and ferroptosis ( 41 ); however, it is also reported that IFN-γ induces the expression of immune checkpoints which may lead to an immune-suppression microenvironment, and this was consistent with our further analysis about the immune microenvironment ( 42 44 ). Taken together, our results suggested that the IFN-γ response pathway might mainly contribute to the immune-suppression microenvironment in glycerolipid metabolism-activated colon cancer, other than antitumor effect.…”
Section: Discussionsupporting
confidence: 90%
“…These modified phospholipids are more sensitive to oxidative damage and thereby enhance tumor sensitivity to ferroptosis [33,34]. Additionally, IFNγ can also enhance the tumor-eliminating potential of CD8+ T cells in a wide range of malignancies, suggesting a positive feedback between CD8+ T cells and IFNγ [35]. Nonetheless, it requires further investigation whether CD8+ T cells could trigger ferroptosis in a IFN-γ-independent manner.…”
Section: Ferroptosis Within the Timementioning
confidence: 99%
“…human interferon (IFN-γ) plays a role in immune evasion and tumor growth, as it stimulates the expression of immunosuppressive molecules, such as B7-H1 (PD-L1), arginase, and indoleamine 2,3-dioxygenase (IDO), in the tumor microenvironment (Diskin et al, 2020). IFN-γ signaling plays a therapeutic role because it enhances the immune system against cancer by inhibiting the growth of many cancer cells including breast cancer cells (García-Tuñón et al, 2007), and It has also a role in promoting cancer development and immune evasion, so IFN-γ is considered to have a dual role (Du et al, 2021).…”
Section: Il-1βmentioning
confidence: 99%